In-Depth Mutational Analysis of the Promyelocytic Leukemia Zinc Finger BTB/POZ Domain Reveals Motifs and Residues Required for Biological and Transcriptional Functions - Melnick, Ari (American Society for Microbiology, 2000)
The promyelocytic leukemia zinc finger (PLZF) protein is a transcription factor disrupted in patients with t(11;17)(q23;q21)-associated acute promyelocytic leukemia. PLZF contains an N-terminal BTB/POZ domain which is required for dimerization, transcriptional repression, formation of high-molecular-weight DNA-protein complexes, nuclear sublocalization, and growth suppression. X-ray crystallographic data show that the PLZF BTB/POZ domain forms an obligate homodimer via an extensive interface. In addition, the dimer possesses several highly conserved features, including a charged pocket, a hydrophobic monomer core, an exposed hydrophobic surface on the floor of the dimer, and two negatively charged surface patches. To determine the role of these structures, mutational analysis of the BTB/POZ domain was performed. We found that point mutations in conserved residues that disrupt the dimer interface or the monomer core result in a misfolded nonfunctional protein. Mutation of key residues from the exposed hydrophobic surface suggests that these are also important for the stability of PLZF complexes. The integrity of the charged-pocket region was crucial for proper folding of the BTB/POZ domain. In addition, the pocket was critical for the ability of the BTB/POZ domain to repress transcription. Alteration of charged-pocket residue arginine 49 to a glutamine (mutant R49Q) yields a domain that can still dimerize but activates rather than represses transcription. In the context of full-length PLZF, a properly folded BTB/POZ domain was required for all PLZF functions. However, PLZF with the single pocket mutation R49Q repressed transcription, while the double mutant D35N/R49Q could not, despite its ability to dimerize. These results indicate that PLZF requires the BTB/POZ domain for dimerization and the charged pocket for transcriptional repression.